DOI: 10.4018/978-1-5225-3808-0.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Media, Social Media, and the Securitization of Mental Health Problems in Nepal

Abstract: This chapter attempts to unfold the trend and nature of mainstream and social media coverage on mental health issues in Nepal through suicide case of Yama Buddha, a popular musician. Using the securitization theory and concepts of threat construction and threat neutralization, major findings through content analysis and key informant interviews reveal reputed mainstream media following cautious route towards threat neutralization and therefore, maintaining a level of journalistic professionalism. However, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…There are many reasons for this, including the absence of a child and adolescent mental health policy, poor child and adolescent mental health services (there is only one outpatient child and adolescent mental health clinic in the whole country and no inpatient facilities), as well as an acute shortage of child and adolescent psychiatrists and allied professionals (only one child and adolescent psychiatrist in the whole country). Furthermore, no specialized postgraduate training in child and adolescent psychiatry is available in Nepal and limited research is performed [4, 1518]. The Government of Nepal has allocated less than 1% of its total health budget for mental health; child and adolescent mental health services receive a negligible portion of this amount [18, 19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons for this, including the absence of a child and adolescent mental health policy, poor child and adolescent mental health services (there is only one outpatient child and adolescent mental health clinic in the whole country and no inpatient facilities), as well as an acute shortage of child and adolescent psychiatrists and allied professionals (only one child and adolescent psychiatrist in the whole country). Furthermore, no specialized postgraduate training in child and adolescent psychiatry is available in Nepal and limited research is performed [4, 1518]. The Government of Nepal has allocated less than 1% of its total health budget for mental health; child and adolescent mental health services receive a negligible portion of this amount [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no specialized postgraduate training in child and adolescent psychiatry is available in Nepal and limited research is performed [4, 1518]. The Government of Nepal has allocated less than 1% of its total health budget for mental health; child and adolescent mental health services receive a negligible portion of this amount [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Available mental health services in South-East Asia tend to be urban-centered and hospital-based, with the result that 80%-90% of the population has no access to treatment. The number of people who commit suicide is higher than the number who die because of road accidents, terrorism, and HIV/AIDS (Uprety & Lamichhane, 2016). The World Health Organization (2001) says that over 90% of suicide cases relate to mental disorders and that more than two-thirds of all suicides are preventable.…”
Section: Introductionmentioning
confidence: 99%
“…In a co-relational comparative study on knowledge and attitude towards mental illness and health among the urban and rural communities in Nepal, Singh et al (2013) found that adults residing in urban had more knowledge about mental illness than adults of rural communities. In Nepal, although there are no accurate data on the prevalence of mental illness, small-scale studies have indicated the prevalence to be as high as 37.5% in rural communities and approximately 30% of the population of Nepal suffers from psychiatric problems (Uprety & Lamichhane, 2016). According to Nepal police data (2074/75), 5346 people committed suicide and around 14-15 people died every day by committing suicide on average.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation